Определение качественного состава экстрактов можжевельника ложноказацкого методом газовой хромато-масс спектрометрии - Савельева, Ольга Валерьевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
In this work, chromatographic conditions for the separation of key and minor components of oil extracts of Juniperus Pseudosabina are developed. A technique for quantitative and qualitative determination of the key components of oil extracts has been developed and their quantitative content in the presented samples has been determined. The results of a study of various types of biomass sample preparation on the efficiency of extraction of compounds from juniper needles with supercritical CO2 with ethanol as a co-solvent and with the maceration method with methanol as a solvent were presented.